Acquired Vitamin B12 Deficiency: Cutaneous Hyperpigmentation and Hepato-Splenomegaly in Megaloblastic Anaemia / Pancytopenia Reported in a 15-Month-Old Boy - AlKateb, Faten Ahmad; AlEidan, Ahmed Mohammed; AlGahtani, Layla Bidah; AlHowiati, Noura Muteeb; AlSwayyed, Aziza Fayez; AlAreefy, Abdulaziz Khaled; AlGhofaily, Mazen Mohammed (International Journal of Innovative Research in Medical Science, 2020)
Megaloblastic Anemia (MA) embraces various conditions with a functioning or a depressed marrow. Hence, in the light of this group of anemia, several observations were made linking it to cutaneous hyperpigmentation. Thus, in combination of both and in the presence of Pancytopenia, we report an atypical clinical image of Acquired vitamin B12 deficiency consistent with the above-mentioned description in a paediatric patient.